The impact of financial crisis on Malaysia's banking industry / Muhammad Hakim Shamsul Bahari - Shamsul Bahari, Muhammad Hakim (2017)
The aim of this study is to examine the impacts of the global financial crisis on Malaysian's banking industry (profitability). The profitability of banks is affected by few factors such as net interest margin, sales growth, capital adequacy, asset quality, earning, liquidity and also the size of the banks. By measuring the profitability by looking at the Return on Asset (ROA) and Return on Equity (ROE), will give a briefs idea on the effects of those factors on banking sector in Malaysia especially. During the global financial crisis, the overall confidence and stability in the Malaysian financial sector has been preserved, which result from a strong financial sector and unimportant or minor exposure to subprime-related assets and affected counterparties. The financial intermediation process in the Malaysian financial system has remained orderly throughout the period of economic turbulence, with continuing flows of credit to the real economy. During that time, Malaysia does not insulated from the global economic downturn.